Integration Between Pancasila Education With Historical And Cultural Education - Anang Dony Irawan; Devy Afriska Widyasari (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2023)
Pancasila education is the basis of education for Indonesian citizens in understanding the ideology of Pancasila. Without understanding the origins of the formation of Pancasila, an understanding of the ideology of Pancasila cannot be known in its entirety. Pancasila has life values ​​taken from Indonesian history and culture, so it can be seen that in understanding the Pancasila ideology, it is also necessary to study Indonesian history and culture which reflects the life of the Indonesian people. In a survey conducted on this issue, it was found that 69.2% of the respondents did not understand the origins of the Pancasila ideology in terms of Indonesian culture and history. Often there are separatist movements that occur because the perpetrators do not embrace the values ​​of Pancasila, it could be because they do not understand the history and culture of Indonesia which is embedded in the Pancasila ideology itself. By integrating Pancasila education with Indonesian history and culture education, it is hoped that students will be able to understand the philosophical and ethical aspects of Pancasila. Act in accordance with the character of the nation so that there will be no problem of differences of opinion that can cause divisions in the Indonesian nation.